The Moderating Role of Teachers’ Efficacy on the Relationship Between the Extent of Implementation of Omnibus Policy on Kindergarten Education and Learners’ Developmental Progress in Rizal and San Jose, Occidental Mindoro - Bandales, John Paulo (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the moderating role of teachers’ efficacy on the relationship between the extent of implementation of the Omnibus Policy on Kindergarten Education and learners’ developmental progress in Rizal and San Jose Districts, Occidental Mindoro. Employing a descriptive correlational design, data were gathered from kindergarten teachers using adapted survey instruments anchored on a 5‑point Likert scale administered through Microsoft Forms. Policy implementation was assessed across five dimensions: learning assessment, instruction, teaching methodologies and strategies, learning resources and instructional materials, learning space and environment, and monitoring and evaluation, while teachers’ efficacy was measured in terms of student engagement, instructional strategies, and classroom management. Learners’ developmental progress was evaluated in five domains: health and motor development, socio‑emotional development, language and literacy, mathematics, and understanding of the environment. Results revealed that policy implementation was generally high, though gaps persisted in resources and learning spaces. Teachers demonstrated moderate to high efficacy, particularly in instructional strategies and classroom management, which positively influenced learner engagement. Learners’ developmental progress was likewise rated high, affirming that effective policy implementation supports holistic growth. Correlation analysis showed mostly negligible relationships among policy implementation, teacher efficacy, and learners’ progress, with only weak but significant link between monitoring and evaluation and language and literacy. Regression analysis confirmed that teacher efficacy did not moderate the relationship between policy implementation and learner outcomes, suggesting that other contextual or professional factors may shape how policy translates into developmental progress. These findings highlight that policy frameworks alone are insufficient; their effectiveness depends on multiple interacting elements within the teaching‑learning environment. The study underscores the importance of continuous capacity building, resource provision, and responsive leadership to sustain quality kindergarten education, offering insights for DepEd, school heads, and teacher training institutions in refining support systems and professional development programs to ensure equitable and developmentally appropriate learning experiences for Filipino children.